2018
DOI: 10.1186/s40249-018-0502-8
|View full text |Cite
|
Sign up to set email alerts
|

Improving immunization capacity in Ethiopia through continuous quality improvement interventions: a prospective quasi-experimental study

Abstract: BackgroundStrong scientific evidence is needed to support low-income countries in building effective and sustainable immunization programs and proactively engaging in global vaccine development and implementation initiatives. This study aimed to implement and evaluate the effectiveness of system-wide continuous quality improvement (CQI) interventions to improve national immunization programme performance in Ethiopia.MethodsThe study used a prospective, quasi-experimental design with an interrupted time-series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 32 publications
0
41
0
Order By: Relevance
“…Recently, attention has shifted to improving services by developing the capabilities and capacity of organizations through building their knowledge, skills, and infrastructure [74]. The focus on system-level quality improvement has resulted in CQI methods being identified, and increasingly used, as an approach to enhance the quality of care and reduce costs [3][4][5][6][7][8][9]72]. Despite its effectiveness within industrial and manufacturing sectors, it remains unclear whether CQI could be successfully employed in the health care sector.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, attention has shifted to improving services by developing the capabilities and capacity of organizations through building their knowledge, skills, and infrastructure [74]. The focus on system-level quality improvement has resulted in CQI methods being identified, and increasingly used, as an approach to enhance the quality of care and reduce costs [3][4][5][6][7][8][9]72]. Despite its effectiveness within industrial and manufacturing sectors, it remains unclear whether CQI could be successfully employed in the health care sector.…”
Section: Discussionmentioning
confidence: 99%
“…Improving the quality and safety of health care is a priority of governments, health care workers, and the public [1,2], with efforts often focused on investment in changes to the way health care is organized and delivered (system-level quality improvements) [3,4]. While there are many different approaches that may be taken, continuous quality improvement (CQI) has received considerable attention within health care [5] as a way to enhance the quality of care and reduce costs [6][7][8][9]. The use of CQI in health care has evolved since the 1990s, using quality control techniques and management theories employed in the industrial and manufacturing sectors [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Health worker training plays an important role in improving overall performance including vaccination coverage [ 15 , 16 ]. Other studies and program reviews have also shown the critical role of human resource in immunisation program delivery [ 17 - 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health worker training plays an important role in improving overall performance including vaccination coverage [ 16 , 17 ]. Other studies and program reviews have also shown the critical role of human resource in immunisation program delivery [ 18 - 20 ]. In the 20 program reviews in this sub-region, capacity gaps are also reflected in the lack of clear managerial tools (e.g., terms of reference, job descriptions and standard orientation/training for newly assigned focal persons).…”
Section: Discussionmentioning
confidence: 99%